Foot-and-mouth disease vaccine potency testing in cattle using homologous and heterologous challenge strains: Precision of the "Protection against Podal Generalisation" test - Goris, N. (2008)
The level of protection conferred by foot-and-mouth disease (FMD) vaccines in primovaccinated animals primarily depends on the potency of the vaccine and the relatedness of the vaccine strain and circulating field isolate. The "Gold Standard" FMD vaccine potency test is the in vivo test performed in the target species. The objective of the study was to determine the precision of the in vivo "Protection against Podal Generalisation" (PPG) FMD vaccine potency test in cattle using homologous (vaccine quality control) and heterologous (vaccine matching) viral challenge. The overall level of protection induced by the A24 Cruzeiro/Brazil/55 vaccine used in six homologous PPG tests was 88.5%. Vaccine accordance (VACC) and vaccine concordance (VCON) were estimated to be 75.9% and 73.7%, respectively. In four heterologous challenge PPG tests, the overall level of cross-protection induced by the A24 Cruzeiro/Brazil/55 vaccine against A Argentina/2001 challenge was 26.6%, with VACC and VCON values of 65.7% and 59.2%, respectively. Results indicate that the homologous PPG test is more reliable than the European Pharmacopoeia potency test, but that a larger number of animals should be used in order to increase the test's statistical power. In this regard, indirect alternative tests for vaccine potency and vaccine matching merit consideration. © 2008 Elsevier Ltd. All rights reserved.